2017
DOI: 10.1080/14767058.2017.1407310
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal complications are associated with the postnatal airway host response and microbiota in intubated preterm infants

Abstract: Airway protein profiles in seven days old mechanically ventilated preterm infants are associated with important antenatal events and unique airway microbial communities. These relationships may reveal new mechanisms by which antenatal events impact the course and outcomes of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Emerging data have highlighted that diverse microbial populations inhabit the respiratory tract, previously considered a sterile compartment [71]. A recent clinical trial examining tracheal aspirates of 71 mechanically ventilated preterm newborns showed important associations between antenatal events, the host airway immune response and airway microbiota [72]. A recent meta-analysis showed that Ureaplasma species colonization was significantly associated with the development of BPD, a chronic lung disease of prematurity leading to life-long limitations in lung function [73].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…Emerging data have highlighted that diverse microbial populations inhabit the respiratory tract, previously considered a sterile compartment [71]. A recent clinical trial examining tracheal aspirates of 71 mechanically ventilated preterm newborns showed important associations between antenatal events, the host airway immune response and airway microbiota [72]. A recent meta-analysis showed that Ureaplasma species colonization was significantly associated with the development of BPD, a chronic lung disease of prematurity leading to life-long limitations in lung function [73].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…The airway of the preterm infant is not sterile at birth and its microbiome is highly influenced by the microbiome of the amniotic fluid. Differences in colonization and clinical parameters allow the categorization into disease clusters, which are predictive for the clinical course and outcome [ 64 ]. Reduced microbial diversity at birth, initial abundance of ureaplasma species in tracheal aspirates of ventilated preterm infants, and more pronounced changes in the longitudinal microbial community are associated with higher severity of BPD.…”
Section: Microbiota Of the Airways And Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…An interesting study by Wagner et al [ 35 ] assessed the airway response in mechanically ventilated preterm infants by examining 12 proteins in tracheal aspirates collected at 7 days of age. Infants were categorized into three clusters based on protein profiles: Cluster 1 had high levels of most proteins, Cluster 2 showed a mix of high proinflammatory and low anti-inflammatory proteins, and Cluster 3 had low levels of all proteins.…”
Section: Resultsmentioning
confidence: 99%